Comparison of frames in social networks of the 2016 and 2021 elections in Peru: the case of candidates Fujimori and Mendoza - Cohaila-Ramos , Edwin (Universidad Politécnica Salesiana (Ecuador), 2023)
This article compares the publications on social networks of the candidates Verónika Mendoza and Keiko Fujimori in the electoral processes of 2016 and 2021, the only candidates who participated in both processes. For this comparison, the framing theory was used, having as cutoff periods before and after the electoral debates. The publications in social networks were classified into thematic, strategic and positional frames. The interest of the comparison lies in observing if the electoral debate, a privileged event to show proposals and government plans, envisions a change in the type of framing of the candidates. It is observed that the publications of the candidates envision different framing positions, but the debate does not change the tenor of the publications, favoring strategic frames over positional and thematic ones.